Kualitas Air Minum Isi Ulang Pada Depot Di Wilayah Kerja Puskesmas Dahlia Kota Makassar - Alfina Baharuddin; La Ode Rangga (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2017)
The quality of drinking water consumed should be eligible. Based on data obtained from the Department of Health Makassar number of diarrhea patients in the District Panakkukang as many as 2,753 people. While the quality of water taps for the District Panakkukang including clean water class D category is very bad because it found the bacteria Escherichia coli > 1100 cells / 100ml. The study aims to determine the content of Escherichia coli in DAMIU in District Panakkukang Makassar.This research uses observational analytic with cross sectional approach. Population of 81 de-pots drinking water, sampling was done by purposive sampling at 22 water depots then examined and analyzed in the laboratory.The results showed that of the 22 samples studied contained 20 AMIU eligible and 2 AMIU are not eligible. This happens because the used processing equipment functioned properly. The sam-ples were positive for Escherichia coli bacteria in addition to the sanitary conditions around the depot that bad either condition processing equipment used do not function and some processing tools has been severely damaged. The results of the analysis showed no relationship between equipment pengolahan drinking water with Escherichia coli p value 0,026 and there was no corre-lation between the condition of the drinking water treatment, hygiene condition handlers and also raw water with Escherichia coli p value 1.000.The Suggested to the owner DAMIU in Sub Panakkukang already qualified drinking water quali-ty based on the Minister of Health in 2010 in order to keep the quality of drinking water produced and for DAM produced do not qualify for more attention to processing equipment used and re-place all the tools that are not feasible used or expired.Keyword : MPN E.coli, Hygiene sanitation, DAMIU